CULTURAL DEVELOPMENT IN EDUCATION - Indah Etika Putri; Firman; Riska Ahmad (Yayasan Citra Dharma Cindekia, 2021)
Education and culture are two interrelated things. Education is always changing along with the development of culture. Because education is a process of delivering cultural values (education is reflective). Education is gradual, meaning that it is always changing according to the needs of cultural development. These two attributes are closely related to each other. Culture is a mirror of a nation, differences in teaching systems, content of teaching, education, etc. are mirrors that reflect the level of education and culture. Education and culture are interrelated, namely education can form educated people or people, and culture can also guide humans to live according to the rules or norms that become the norms of life.